2011
DOI: 10.5941/myco.2011.39.4.272
|View full text |Cite
|
Sign up to set email alerts
|

Breeding of New Strains of Mushroom by Basidiospore Chemical Mutagenesis

Abstract: Chemical mutagenesis of basidiospores of Hypsizygus marmoreus generated new mushroom strains. The basidospores were treated with methanesulfonate methylester, an alkylating agent, to yield 400 mutant monokaryotic mycelia. Twenty fast-growing mycelia were selected and mated each other by hyphal fusion. Fifty out of the 190 matings were successful (mating rate of 26.3%), judged by the formation of clamp connections. The mutant dikaryons were cultivated to investigate their morphological and cultivation character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…To generate more genetic diversity, the basidiospores were treated with 0.01 vol% methymethane sulfonate (MMS; Sigma-Aldrich Co., St. Louis, MO, USA), an alkylating agent, using a previously described method [ 13 ]. The survival rate of the germinated spores was 93% at 0.01 vol% MMS.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To generate more genetic diversity, the basidiospores were treated with 0.01 vol% methymethane sulfonate (MMS; Sigma-Aldrich Co., St. Louis, MO, USA), an alkylating agent, using a previously described method [ 13 ]. The survival rate of the germinated spores was 93% at 0.01 vol% MMS.…”
Section: Methodsmentioning
confidence: 99%
“…When the newly formed dikaryotic mycelial strains are ready, they are cultivated to produce fruiting bodies, which are used to screen for strains with good commercial and cultivation traits. However, dikaryotic strains do not always produce fruiting bodies [ 12 , 13 ]. The fruiting rate of the newly formed strain, which is the ratio of fruiting body-forming strains per total dikaryotic strains, is highly dependent on environmental conditions and mushroom species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, no other significant variation was recorded in terms of biological efficiency in any of the mutants (Table 1). Lee et al (2011) observed that basidiospores treated with chemical mutagens showed a change in primordial initiation resulting in reduced yield. Strain improvement in three isolates of P. ostreatus viz.…”
Section: Fruiting Behavior Of Uv and Ems Treated Culturesmentioning
confidence: 99%
“…In order to use the mycelia of S. crispa as a β-glucan producer, development of a fast-growing strain with high β-glucan content became essential. Our previous work provided evidence indicating that chemical mutagenesis was an effective method for generation of mutant strains with desirable properties [ 15 ]. Treatment of basidiospores with an alkylating agent and subsequent mating resulted in generation of a mushroom with diverse morphological characteristics.…”
mentioning
confidence: 99%